Electrophysiological and 99mTc-HMPAO-SPECT studies in Menkes disease - Sztriha, L; Janáky, M; Kiss, J; Buga, K (Brain & development (Tokyo. 1979), 1994)
A diagnosis of Menkes kinky hair disease was made in two brothers who had typical clinical symptoms and laboratory findings. The older one, 11 months old at the time of diagnosis, showed an EEG pattern of low amplitude and slow waves. Visual evoked potentials (VEPs) were absent, brainstem auditory evoked potentials (BAEPs) were abnormal. Regional cerebral blood flow (rCBF) studied by hexamethylpropyleneamine oxime single photon emission computed tomography (99mTc-HMPAO-SPECT) revealed reduced blood flow in both frontal and the right temporal regions. The younger boy, followed from birth, started seizures at the age of 3 months and had a hypsarrhythmia-like EEG. BAEPs were abnormal with prolongation of the latencies at the age of 12 months, while VEPs were near normal at 6 months, but disappeared by the age of 18 months. 99mTc-HMPAO-SPECT revealed an unexpected left parietal hyperperfusion.